Synergistic effects of CuI doping on enhancing thermoelectric performance for n-type Bi2O2Se fabricated by mechanical alloying. (1st March 2023) - Zhou, Zhifang; Liu, Rui; Yang, Yueyang; Zheng, Yunpeng; Wei, Bin; Zhang, Wenyu; Zou, Mingchu; Han, Jian; Liu, Yiqian; Lan, Jinle; Nan, Ce-Wen; Lin, Yuan-Hua
Abstract: The extremely low electrical conductivity and time-consuming preparation methods limit potential practical applications for Bi2 O2 Se-based thermoelectric materials. To solve these problems, a fast preparation method of combining mechanical alloying (MA) with spark plasma sintering (SPS) has been successfully adopted to synthesize CuI-doped Bi2 O2 Se in this work. The electrical conductivity was largely improved from 3 S cm −1 to 296 S cm −1 at 823 K attributed to the optimized carrier concentration. Meanwhile, an extremely low lattice thermal conductivity value of 0.39 W m −1 K −1 at 823 K was achieved by intensive phonon scatterings from point defects and dense grain boundaries. Consequently, an enhanced ZT value reached 0.45 at 823 K, which resulted in ∼380% improvement over that of the pristine Bi2 O2 Se prepared by solid-state reaction (SSR). This work opens a new gate for synergistically optimizing electron and phonon transport properties for Bi2 O2 Se-based thermoelectric materials. Graphical abstract: Image, graphical abstract